Alkylpurine glycosylase D employs DNA sculpting as a strategy to extrude and excise damaged bases. - Bradley Kossmann (Public Library of Science (PLoS), 2014)
Alkylpurine glycosylase D (AlkD) exhibits a unique base excision strategy. Instead of interacting directly with the lesion, the enzyme engages the non-lesion DNA strand. AlkD induces flipping of the alkylated and opposing base accompanied by DNA stack compression. Since this strategy leaves the alkylated base solvent exposed, the means to achieve enzymatic cleavage had remained unclear. We determined a minimum energy path for flipping out a 3-methyl adenine by AlkD and computed a potential of mean force along this path to delineate the energetics of base extrusion. We show that AlkD acts as a scaffold to stabilize three distinct DNA conformations, including the final extruded state. These states are almost equivalent in free energy and separated by low barriers. Thus, AlkD acts by sculpting the global DNA conformation to achieve lesion expulsion from DNA. N-glycosidic bond scission is then facilitated by a backbone phosphate group proximal to the alkylated base.